2014
DOI: 10.1111/jtm.12147
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Know About Medical Tourism? A Review of the Literature With Discussion of Its Implications for the UK National Health Service as an Example of a Public Health Care System

Abstract: It demonstrates the importance of quality standards and holds lessons as the UK and other EU countries implement the EU Directive on cross-border care. Lifting the private-patient-cap for NHS hospitals increases potential for growth in inbound medical tourism; yet no research exists on this. Research is required on volume, cost, patient motivation, industry, and on long-term health outcomes in medical tourists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 47 publications
3
91
0
3
Order By: Relevance
“…From this perspective, further investigation of the experiences of paid caregivers in medical tourism is also warranted, including both medical and nonmedical caregivers (e.g., coordinators, translators, cleaning staff, drivers). In addition, medical tourism provides a key example of marketization in the provision of care, as destinations compete to attract consumers of medical services (Connell, 2013;Hanefeld et al, 2013;Lunt et al, 2014). Research on the trade in global health services has highlighted the ethical and equity impacts of medical tourism in destination countries (Meghani, 2010;Cohen, 2012;Chen and Flood, 2013;Turner, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From this perspective, further investigation of the experiences of paid caregivers in medical tourism is also warranted, including both medical and nonmedical caregivers (e.g., coordinators, translators, cleaning staff, drivers). In addition, medical tourism provides a key example of marketization in the provision of care, as destinations compete to attract consumers of medical services (Connell, 2013;Hanefeld et al, 2013;Lunt et al, 2014). Research on the trade in global health services has highlighted the ethical and equity impacts of medical tourism in destination countries (Meghani, 2010;Cohen, 2012;Chen and Flood, 2013;Turner, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Medical tourists are individuals who travel abroad with the intention of accessing private medical outside the context of referral from their home health care system (Hopkins et al, 2010;Hanefeld et al, 2013). To date, reliable quantitative data about medical tourism are limited (Connell, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…58,59 Despite developing strategic alliances among hospitals and healthcare centers, the inability of many healthcare systems to cope with the increased demand often leads to poor healthcare services, high costs, and long waiting lists. 60,61,62,63,64 With the decrease in cross-border communication through the Internet (e.g., websites, emails) and cheaper air travel, 65 reported that healthcare and health treatments will be the world's largest industry while tourism will become the world's second largest industry by 2022. Harker and Egan 77 indicated that the scope, approaches, and applications of relationship marketing should be examined closely in order to understand the impact of relationship on the medical tourism industry.…”
Section: Research In Medical Tourism and Relationship Marketingmentioning
confidence: 99%
“…The legal aspects of this activity are not entirely clear; neither relevant medical study in the international scientific literature can be found. Some aspects of these patients, such as organ transplants, surrogacy or commodification involve transcendental international legal and ethical challenges [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%